ROOT CANAL LENGTH MEASUREMENT IN TRANSPARENT RESIN TOOTH MODELS USING AN ENDODONTIC MOTOR WITH INTEGRATED ELECTRONIC APEX LOCATOR IN 0.9% SALINE SOLUTION (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the accuracy of apical foramen localization by the electronic apex locator integrated into an Ai-Motor endodontic motor on transparent 3D-printed teeth in a 0.9% saline environment.Methods: Cone-beam computed tomography (CBCT) was used to scan three extracted human premolars obtained from patients undergoing orthodontic treatment. Transparent 3D-printed teeth with pre-prepared access cavities were placed in a transparent plastic container filled with saline solution and mounted on the specimen stage of a microscope. An endodontic handpiece equipped with a reciprocating instrument was rigidly fixed to the specimen stage of another microscope. The instrument was introduced into the root canal of the printed tooth to locate the apical foramen under two operating modes: automatic stop at the apical foramen and automatic reverse rotation upon reaching the apical foramen. Differences in the position of the microscope’s fine micrometer knob between measurements were recorded and compared. Bland–Altman plots were used to assess the agreement between the two apex localization modes.Results: There were no statistically significant differences in measurement outcomes between the two operating modes, and no proportional or fixed bias was detected in the Bland–Altman analysis.Conclusion: Apical foramen localization using both operating modes of the Ai-Motor can be performed accurately on transparent 3D-printed teeth.Keywords: electronic apex locator (EAL), resin tooth, root canal length
Keywords: electronic apex locator (EAL), resin tooth, root canal length